2017
DOI: 10.2147/cpaa.s147835
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prescribed medications and pattern of distribution for potential drug–drug interactions among chronic kidney disease patients attending the Nephrology Clinic of Lagos University Teaching Hospital in Sub-Saharan West Africa

Abstract: IntroductionLife expectancy has increased significantly among chronic kidney disease (CKD) patients due to the extensive use of polypharmacy practice for medication prescriptions. This predisposes them to potential drug–drug interactions (DDIs), which can lead to an increase in morbidity, mortality, length of hospital stay, and health care cost.MethodsThis was a 30-month retrospective study that reviewed the medical case records of consenting adult CKD patients from January 2014 to June 2016. The Medscape drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 24 publications
8
33
4
2
Order By: Relevance
“…Table 7 shows previous reports in which the prevalence and severity of pDDIs has been evaluated on CKD patients. It is remarkable that there are two studies published in 2017 that were carried out in different hospitals in Nigeria, with different numbers of individuals, but their results are practically identical despite using different analysis tools [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 7 shows previous reports in which the prevalence and severity of pDDIs has been evaluated on CKD patients. It is remarkable that there are two studies published in 2017 that were carried out in different hospitals in Nigeria, with different numbers of individuals, but their results are practically identical despite using different analysis tools [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the prevalence and severity of potential drug–drug interactions (pDDIs) using different drug–drug interaction programs among CKD patients from Brazil [ 10 , 11 ], India [ 12 , 13 ], Pakistan [ 14 ], Palestine [ 15 ], and Nigeria [ 16 , 17 , 18 , 19 ]; however, there are no published studies evaluating the prevalence of pDDIs among CKD patients in any European country.…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration should be made for potential interactions with CNS drugs such as alprazolam that can enhance the PD effects of the drug in those patients [41,42]. Generally, CNS and CVD medications (including statins and anti-platelet, anticoagulant drugs) can be the possible or probable reason for ADE/ADRs in the current population, as also estimated from the Naranjo scale results ( Figure 5) [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…A study of only 79 such patients showed that the frequency of pDDIs at discharge from the general neurological department was 72% [15], while in patients with stroke (ischemic and hemorrhagic), the prevalence of pDDIs was 61%-89.5% [7,8]. The highest frequency of pDDIs (98% for highly significant interactions), was observed in patients from the ICU among antimicrobial drugs [16], and 95.9% in patients with CKD [17]. A review about the prevalence of pDDIs showed that their frequency was 67% in the ICU and 33% in general departments [1].…”
Section: Discussionmentioning
confidence: 99%